The time is now : creating community through social justice artmaking - Boske, Christa (Emerald Publishing Limited : INFORMATION AGE PUBLISHING, INC., 2022)
"High school students, teachers, community members, and leaders come together in this innovative book to share the profound influence of artmaking and justice-oriented work. Authors paint vibrant images of being empowered and engaging in social change. Throughout their art-based meaning making, authors pose critical questions and unlock possibilities. Their first-tellings regarding the power of art provide readers with a lens to understand how they navigate injustices they endure and ways in which artmaking is a vehicle for transformation. Authors emphasize how artmaking bridges relationships and brings diverse community members together with purpose. Together, they engage in new understandings of self and other. Authors identify how their arts-based collaborations publicly showcase their justice-oriented work, but more importantly, promote possibility and hope. Youth explore how artmaking plays a vital role in promoting collective efficacy and engaging diverse communities in social transformation. Artmaking mobilizes people. And once activated, these authors utilize their newly cultivated communities to foster justice-oriented work throughout schools and communities. Their justice-oriented artmaking affords community members opportunities to respond in new ways by embracing community strengths and students' lived experiences. This authentic collaboration empowers the artmaker and community to promote justice-oriented work and practices centered on diversity and inclusivity. Their artmaking is a call for change"-- Provided by publisher.
Keywords: Arts in education -- Social aspects -- United States.; Arts -- Study and teaching -- United States.; Social justice and education -- United States.; Teaching -- Social aspects -- United States.; Social justice in art.; Education -- Teaching -- Subjects -- Arts & Humanities.; Teaching of a specific subject.; Educational: Arts, general.; Educational: Humanities and social sciences, general.; elektronické knihy; electronic books